2015
DOI: 10.1097/moh.0000000000000119
|View full text |Cite
|
Sign up to set email alerts
|

Is it time to change conventional consolidation chemotherapy for acute myeloid leukemia in CR1?

Abstract: Genetic risk assessment, monitoring of minimal residual disease in first remission, use of targeted agents, and the newer transplant strategies all have the potential to 'personalize' PRT choice in the AML patient. The clinical value of these novel interventions awaits validation in prospective, risk-adapted clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 87 publications
1
3
0
Order By: Relevance
“…9,10 The 5-year OS was 43%, and for patients with a ckit mutation, the OS was 40%. 11,12 The present study showed that 58 patients with AML with CBFB-MYH11 had a CR rate of 98Á3% after one course of treatment and a CR rate of 100% after two cumulative courses of treatment, showing good efficacy.…”
Section: Discussionsupporting
confidence: 50%
“…9,10 The 5-year OS was 43%, and for patients with a ckit mutation, the OS was 40%. 11,12 The present study showed that 58 patients with AML with CBFB-MYH11 had a CR rate of 98Á3% after one course of treatment and a CR rate of 100% after two cumulative courses of treatment, showing good efficacy.…”
Section: Discussionsupporting
confidence: 50%
“…Although CBF-AML patients have better prognosis, only approximately 40–60% are cured by standard therapy using a backbone of high dose cytarabine treatment in combination with an anthracycline 53,54 which is essentially unchanged for the past 40 years 55 . A study of 285 newly diagnosed patients with AML showed that high dose cytarabine treatment provides the best outcome for CBF-AML patients with 50% demonstrating CR after 5 years 56 .…”
Section: Treatmentmentioning
confidence: 99%
“…A study with patients (up to 45 years) in complete remission (CR) showed that though there is no difference in disease free survival rate for patients with inv(16) and t(8;21), when allo-or auto-SCT were performed after intensive consolidation therapy, the OS was better for younger patients receiving allo-SCT 62 . HSCT is not necessary in first CR for patients with CBF leukemias unless they have relapsed, refractory or otherwise high risk disease 54,63 . However, patients older than 75 years have very poor prognosis and patients over 60 years may be considered for allo-HSCT 28 .…”
Section: Treatmentmentioning
confidence: 99%
“…However, at times, many obstacles to further progress present themselves, including limitations in funding for laboratory and clinical studies, as well as government and institutional regulatory impediments. Wolach and Stone [7] review potential changes in our approach to consolidation therapy. Nevertheless, the intellectual satisfaction of important advances in understanding human disease carries the day.…”
mentioning
confidence: 99%